Quality planting material of tubers pays - George, James; Sunitha, S.; Ravindran, C. S. (Indian Horticulture, 2019)
Since tuber crops are clonally propagated, spread of disease becomes very easy. Another serious problem is the poor multiplication ratio unlike cereals and pulses. While in cereals, the multiplication ratio is as high as 1:140, in cassava it is 1:10, in Amorphophallus it is 1:3, in yams it is 1:4 and in colocasia the multiplication ratio is 1:20. This low multiplication ratio is mainly responsible for undue delay for released high-yielding varieties to reach the farmers. Minisett technique (cutting stem/tuber/corm into pieces of optimum size for sprouting) developed at CTCRI, Thiruvananthapuram, is an effective and viable technology. It is farmer-friendly and has since then proved to be quite effective in rapidly producing quality planting material in tuber crops. The minisett techniques in major tuber crops are briefly presented here.